Disaster Diplomacy of South Korea toward North Korea as Efforts to Create Peace in the Korean Peninsula (2017 – 2020) - Syafiq Rizqullah, Muhammad Fawwaz; Tristofa, Luna; Ramadhanti, Devia Farida (Nation State: Journal of International Studies, 2021)
This paper aims to analyze the reason why South Korea as a North Korea rival in the Koreanpeninsula willing to give aid toward North Korea. The tension in Korean peninsula has happened since a long time ago especially after the cold war between USA & USSR. The conflict event become worst because of North Korea always threatening South Korea by testing the Nuclear missile. Despite of what North Korea done in the region, South Korea still gave abundance of aid in term of health assistance, food, and others basis of human necessity. By using qualitative approach and collecting data from credible literature resource and using the concept of disaster diplomacy this research found that South Korea has special type in term of conflict resolution, South Korea often using soft diplomacy and negotiation in order to creating peace. South Korea also believe positive peace diplomacy should be implementing in order make better condition in Korean peninsula. This research also believe that the actor has a big impact in successfully to support better condition between both countries and strengthening the relation. Lastly, this paper proof if in order to win in some competition not always using hard diplomacy or military power.